Capitalism as the Global Social Order: A Critical Perspective - Ivanova, Anna (Волинський національний університет імені Лесі Українки, 2021)
The article studies the concept of the global social order as a subject of social research. The author starts with pointing at the changes in the structure and the character of the today's global social order (acceleration of exchanges and flows, gradual disappearing of a single hegemony, multipolarity) and claims that it is exactly capitalism that becomes a foundation for multipolar but yet unequal constitution of the global order. The article proposes to deal with the global social order as an example of a global subject – alternative to world system or global system – which can be placed in focus of social research. Also, the paper offers a definition to the notions of social order and global social order. Then the author provides several possible classification of the approaches to the study of the global social order, and then moves on to pointing out their mutual positions. The paper considers capitalism as a special form of global social order and suggests to analyze imperialism and neocolonialism as, on the one hand, the products of this order, and on the other hand, as instruments for its legitimation and hegemony. In the further research the suggested model can be used, first, for the improvements in the study of sociology's global subject, and, second, for deepening the knowledge about the process of (re)production of global social order.
Keywords: global social order; capitalism; imperialism; neocolonialism; globalization; 316.33:316.1:316.2